Piracy & plunder : a murderous business - Meltzer, Milton; Waldman, Bruce (New York : Dutton, 2001)
Surveys the history of pirates, why and how they became thieves and killers, the lives they led on sea and on land, the harm they did, and the fates they suffered.
Includes bibliographical references and index.
5-A.
Keywords: Pirates; Hijacking of ships